Analysis of the Health Level of Sharia Savings and Loan Cooperatives in the Regulation of the Minister of Cooperatives - Sudirawarda, Suci Utami; Afif, M. Nur; Aziz, Ayi Jamaludin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Cooperatives act as institutions that are able to collect and create economic strength collectively to achieve a better level of welfare for their members. Regulation of the Minister of Cooperatives and SMEs Number 9 of 2020 stipulates the method of assessing the Cooperative Health Level as a guide to objectively assessing cooperative performance consisting of risk profiles, financial performance and capital. This study aims to analyze the health level of KSPPS BMT Binaul Ummah Bogor City for the 2019-2023 period using a quantitative descriptive approach with primary and secondary data sources. The assessment was carried out based on the concept contained in the Regulation of the Minister of Cooperatives and SMEs Number 9 of 2020 and Technical Instructions Number 15 of 2021, and supported by documentation, interview, and literature study methods. The results of the study showed that this cooperative had a score of 12.00 with a healthy category for risk profiles, a score of 90.00 with a healthy category for financial performance, and a score of 6.90 with a category under special supervision for capital. Overall, the Cooperative obtained a total score of 108.9 with a healthy predicate.